Exploring Competencies That Prepare Occupational Therapy Students for Acute Mental Health Practice: A Document Analysis. - Mkhize, Phakeme Z.; Mpanza, December M.; Naidoo, Deshini; Hilton, Claudia (Occupational Therapy International, 2026)
Occupational therapy graduates in South Africa are increasingly required to practice in acute mental health settings, yet the extent to which current curricula prepare them adequately remains underexplored. This study examined the competencies required for acute mental health occupational therapy practice through a comparative document analysis of four national and international frameworks: the WFOT Minimum Standards (2016), HPCSA Minimum Standards (2024), WHO Recommendations for Occupational Therapy Practice in Mental Health (2024), and WHO mhGAP Intervention Guide (2016), mapped against the University of KwaZulu‐Natal (UKZN) exit‐level outcomes (2024). Seven core competency domains were identified across the frameworks. The UKZN outcomes demonstrated strong alignment in cultural competence and interdisciplinary collaboration, partial alignment in recovery‐oriented practice, assessment skills, therapeutic use of self, and professional resilience, and confirmed gaps in condition‐specific knowledge, risk assessment, trauma‐informed care, crisis intervention, and transition planning. These findings demonstrate that acute mental health competency preparation cannot be achieved through alignment with any single regulatory document, including the HPCSA framework. This therefore calls for both urgent curriculum reform and strengthening of accreditation standards across all South African occupational therapy programs.